2020
DOI: 10.3171/2019.3.jns1963
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an effective implantable pump-infusion system for chronic convection-enhanced delivery of intracerebral topotecan in a large animal model

Abstract: OBJECTIVEIntracerebral convection-enhanced delivery (CED) has been limited to short durations due to a reliance on externalized catheters. Preclinical studies investigating topotecan (TPT) CED for glioma have suggested that prolonged infusion improves survival. Internalized pump-catheter systems may facilitate chronic infusion. The authors describe the safety and utility of long-term TPT CED in a porcine model and correlation of drug distribution through coinfusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Current preclinical studies for therapeutic approaches including, but not limited to, oncolytic viral therapy, immunotherapy, convection-enhanced delivery, fluorescein dyes and laser interstitial thermal therapy in high-grade glioma rely on large animal models with no ability to evaluate therapeutic efficacy in disease models 7 . By using orthotopic intraparenchymal gene transfer in higher-order species, given the advantages of an immunocompetent porcine model, investigators can reasonably adjust transgenes and/or promoters to dissect the disease process and develop translationally relevant systems in a variety of glioma grades and subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current preclinical studies for therapeutic approaches including, but not limited to, oncolytic viral therapy, immunotherapy, convection-enhanced delivery, fluorescein dyes and laser interstitial thermal therapy in high-grade glioma rely on large animal models with no ability to evaluate therapeutic efficacy in disease models 7 . By using orthotopic intraparenchymal gene transfer in higher-order species, given the advantages of an immunocompetent porcine model, investigators can reasonably adjust transgenes and/or promoters to dissect the disease process and develop translationally relevant systems in a variety of glioma grades and subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic profile, immune system, and the size and anatomy of the porcine brain and spinal cord is recognized to better model the human 25,29,31 . For these reasons, device implantation, stereotactic radiosurgery, and intrathecal and intraparenchymal drug delivery have all been performed in pigs 7,27,[32][33][34][35][36] . Furthermore, while the Food and Drug Administration (FDA) has recognized proof-of-principle data on therapeutic efficacy in highly characterized rodent models, the use of large animals is considered critical for clinical relevance.…”
mentioning
confidence: 99%
“…Nevertheless, other preclinical studies have shown promising results [410], and continuous efforts have been made to improve the efficiency of CED, including works in catheter technology and optimal positioning [406]. Recently, a chronic CED administration system was used to infuse the topoisomerase inhibitor topotecan in a pig model for up to 32 days without toxicity [411]. The use of ABC inhibitors has been suggested as a strategy to improve CED and could be further explored.…”
Section: Local Delivery: Polymeric Drug Delivery Systems and Convectimentioning
confidence: 99%
“…They demonstrated that high flow rates up to 4 mL/day lead to large and stable drug volumes distribution during a 32 days treatment period without inducing toxic effects. 172 While more work needs to be done to optimize pulsatile infusion schedules, this study represents an important stepping stone for the refinement of the CED technique in a clinically relevant animal model. 173 Finally, the results of the phase II clinical trial NCT00431561, assessing therapeutic response of recurrent/refractory HGG patients to the administration of an immune-oncology drug candidate with a CED system, were recently published.…”
Section: Convection Enhanced Delivery (Ced)mentioning
confidence: 99%
“…Recently, D'Amico et al 172 successfully validated the effectiveness of an implantable pumpinfusion system for chronic CED of intracerebral topotecan in pigs. They demonstrated that high flow rates up to 4 mL/day lead to large and stable drug volumes distribution during a 32 days treatment period without inducing toxic effects.…”
Section: Convection Enhanced Delivery (Ced)mentioning
confidence: 99%